Genomic Evidence for Cryptic Speciation in Tree Frogs From the Apennine Peninsula, With Description of Hyla perrini sp. nov - Dufresnes, Christophe; Mazepa, Glib; Rodrigues, Nicolas; Brelsford, Alan; Litvinchuk, Spartak N.; Sermier, Roberto; Lavanchy, Guillaume; Betto-Colliard, Caroline; Blaser, Olivier; Borzée, Amaël; Cavoto, Elisa; Fabre, Guillaume; et al. (Frontiers in Ecology and Evolution, 2018)
Despite increasing appreciation of the “speciation continuum”, delimiting and describing new species is a major yet necessary challenge of modern phylogeography to help optimize conservation efforts. In amphibians, the lack of phenotypic differences between closely-related taxa, their complex, sometimes unresolved phylogenetic relationships, and their potential to hybridize all act to blur taxonomic boundaries. Here we implement a multi-disciplinary approach to evaluate the nature of two deeply-diverged mitochondrial lineages previously documented in Italian tree frogs (Hyla intermedia s. l.), distributed north and south of the Northern Apennine Mountains. Based on evidence from mitochondrial phylogenetics, nuclear phylogenomics, hybrid zone population genomics, niche modelling analyses, and biometric assessments, we propose that these lineages be considered distinct, cryptic species. Both mitochondrial and nuclear data affirm that they belong to two monophyletic clades of Pliocene divergence ( 3.5 My), only admixing over a relatively narrow contact zone restricted to the southeast of the Po Plain (50-100km). These characteristics are comparable to similarly-studied parapatric amphibians bearing a specific status. Inferred from their current geographic distribution, the two Italian tree frogs feature distinct ecological niches (<15% of niche overlap), raising questions regarding potential adaptive components contributing to their incipient speciation. However, we found no diagnostic morphological and bioacoustic differences between them. This system illustrates the speciation continuum of Western-Palearctic tree frogs and identifies additional cryptic lineages of similar divergence to be treated as separate species (H. cf. meridionalis). We recommend combined approaches using genomic data as applied here for the future taxonomic assessment of cryptic diversity in alloparapatric radiations of terrestrial vertebrates, especially in controversial taxa. Finally, we formally described the northern Italian tree frogs as a new species, Hyla perrini, sp. nov.